THE EFFECTIVENESS OF MATHEMATICAL LEARNING IN LOGIC COMPETENCY WITH PROBLEM BASED LEARNING THROUGH THE COOPERATIVE MODEL OF TYPE THINK-PAIR-SHARE IN TERM OF STUDENT ACHIEVEMENT AND STUDENT CONFIDENCE OF GRADE X SMA NEGERI 1 DEPOK - Indri Aryanti; Sahid . (Jurnal Pedagogi Matematika, 2017)
The  purpose  of  this  research  were  to  describe  the  effectiveness  of  mathematical  learning  in  logic competency with problem based learning through the cooperative model of type think pair share (TPS) in term of student achievement  and student confidence. This research used quasi-exsperimental with pre-test and post-test control group design. Its population was all students of grade X SMA Negeri 1 Depok. The samples  were  class  XD  as  experiment  class  which  given  problem based  learning  through  the  cooperative model  of  type  TPS  and  class  XB  as  control  class  whivh  given  conventional  learning  approach.  The instruments used in this research were learning instrument, i.e. lesson plan and student worksheet, pre-test and  post-test  as  test  instrument  to  measure  student  achievement,  observation  sheets  and  questionnaire confidence  as  non-test  instrument.  The  hypotheses  testing  used  were  one  sample  t-test  and  independent sample t-test. The results indicated that: (1) mathematics learning with problem based learning through the cooperative  model  of  TPS was  effective in terms  of  student  achievement,  (2)  mathematics  learning  with conventional learning approach was effective in terms of student achievement, (3) mathematics learning with problem  based  learning  through  the  cooperative  model  of  TPS  was  not  effective  in  terms  of  student confidence, (4)  )  mathematics learning  with conventional learning  approach  was  not effective  in terms  of student  confidence,  and  (5)  mathematics  learning  with problem  based  learning  through  the  cooperative model  of TPS  was  not  more  effective than  mathematics learning  with conventional  learning  approach in terms of student achievement.